2021
DOI: 10.1021/acs.est.1c05614
|View full text |Cite
|
Sign up to set email alerts
|

Nanoplastic Transport in Soil via Bioturbation by Lumbricus terrestris

Abstract: Plastic pollution is increasingly perceived as an emerging threat to terrestrial environments, but the spatial and temporal dimension of plastic exposure in soils is poorly understood. Bioturbation displaces microplastics (>1 μm) in soils and likely also nanoplastics (<1 μm), but empirical evidence is lacking. We used a combination of methods that allowed us to not only quantify but to also understand the mechanisms of biologically driven transport of nanoplastics in microcosms with the deep-burrowing earthwor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(17 citation statements)
references
References 92 publications
1
12
0
Order By: Relevance
“…32 By measuring Pd as a proxy for the NPs, they offered a robust method for detecting NPs more easily, sensitively, and quantitatively in complex samples. In terms of application, the fate of NPs in simulated activated sludge processes in a municipal sewage treatment, 33 NP transport through unsaturated porous media, 34 and NP uptake and effects on Gammarus pulex 35 have been demonstrated. Presumably, this technique may provide a new insight into the toxicokinetic properties of NPs and a better understanding of their behavior in aquatic organisms.…”
Section: ■ Introductionmentioning
confidence: 99%
“…32 By measuring Pd as a proxy for the NPs, they offered a robust method for detecting NPs more easily, sensitively, and quantitatively in complex samples. In terms of application, the fate of NPs in simulated activated sludge processes in a municipal sewage treatment, 33 NP transport through unsaturated porous media, 34 and NP uptake and effects on Gammarus pulex 35 have been demonstrated. Presumably, this technique may provide a new insight into the toxicokinetic properties of NPs and a better understanding of their behavior in aquatic organisms.…”
Section: ■ Introductionmentioning
confidence: 99%
“…The main mechanism by which earthworms were harmed by MPs is ingestion, with a notable focus on its effects on earthworm growth (Huerta Lwanga et al, 2016;Huerta Lwanga et al, 2017a). The ingestion of MPs by earthworms affects the earthworm gut bacterial community (Wang H. et al, 2019), and earthworm gut bacteria can promote plastic degradation (Huerta Lwanga et al, 2018), thereby increasing the risk of MPs entering the groundwater (Zhang et al, 2018;Yu et al, 2020;Heinze et al, 2021). Ingestion of MPs may cause mechanical damage to the digestive organisms in earthworms, and Fourier-transform infrared-attenuated total reflectance (FTIR-ATR) spectroscopy and intestinal pathology analyses indicate that MPs can damage the intestinal tract of earthworms (Rodriguez-Seijo et al, 2017).…”
Section: Current Research Hotspotsmentioning
confidence: 99%
“…Furthermore, the uptake of MPs by soil organisms affects digestive processes, resulting in bioaccumulation and biomagnification effects (Wang H. et al, 2019;Li M. et al, 2021;Zhao et al, 2022). Moreover, the activities of soil organisms drive the migration of MPs from the topsoil to the subsoil (Yu et al, 2019), thus increasing the risk of MPs entering groundwater (Zhang et al, 2018;Yu et al, 2020;Heinze et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Earthworms, microarthropods and other bioturbators can accelerate vertical transport of MnPs by creating preferential flow paths (Heinze et al 2021). Some studies have shown that this can lead to MnPs being transported to depths of up to 40-50 cm (Huerta Lwanga et al 2017;Rillig et al 2017;Rodríguez-Seijo and Pereira 2019).…”
Section: Soil and Vadose Zonementioning
confidence: 99%